Scope of tetrazolo[1,5-a]quinoxalines in CuAAC reactions for the synthesis of triazoloquinoxalines, imidazoloquinoxalines, and rhenium complexes thereof - Holzhauer, Laura; Liagre, Chloé; Fuhr, Olaf; Jung, Nicole; Bräse, Stefan (Beilstein Journal of Organic Chemistry, 2022)
The conversion of tetrazolo[1,5-a]quinoxalines to 1,2,3-triazoloquinoxalines and triazoloimidazoquinoxalines under typical conditions of a CuAAC reaction has been investigated. Derivatives of the novel compound class of triazoloimidazoquinoxalines (TIQ) and rhenium(I) triazoloquinoxaline complexes as well as a new TIQ rhenium complex were synthesized. As a result, a small 1,2,3-triazoloquinoxaline library was obtained and the method could be expanded towards 4-substituted tetrazoloquinoxalines. The compatibility of various aliphatic and aromatic alkynes towards the reaction was investigated and the denitrogenative annulation towards imidazoloquinoxalines could be observed as a competing reaction depending on the alkyne concentration and the substitutions at the quinoxaline.
Keywords: click reaction; CuAAC; denitrogenative annulation; imidazole; metal complexes; quinoxaline; tetrazole; triazole